1989
DOI: 10.1099/00221287-135-12-3329
|View full text |Cite
|
Sign up to set email alerts
|

Plasmid-mediated Chloramphenicol Resistance in Staphylococcus hyicus

Abstract: A small plasmid of 3.95 kb, encoding resistance to chloramphenicol (Cm) was detected in three of 33 Staphylococcus hyicus strains. The plasmid in each of the three strains was indistinguishable by Southern-blot hybridization and restriction enzyme analysis. It was shown by curing and by transformation to specify resistance to Cm. A preliminary restriction map of the plasmid, designated pSC2, is presented. Chloramphenicol acetyltransferase was demonstrated by enzyme assay and by SDS-PAGE of cell-free lysates of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
54
0

Year Published

1990
1990
2014
2014

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(56 citation statements)
references
References 23 publications
2
54
0
Order By: Relevance
“…In contrast, the S. hyicus recipients accepted the conjugative aadA-aphD-carrying resistance plasmids. Once again, this is in accordance with previous reports on resistance plasmids in S. hyicus and their structural similarities to resistance plasmids seen in other staphylococcal species from humans and animals [63,71,72,81]. Thus the spread of a certain plasmid or transposon may also be strongly influenced by factors in the host cells, such as restriction/modification systems or other plasmid exclusion systems which in the majority of cases remain to be identified in animal staphylococci.…”
Section: Horizontal Gene Transfersupporting
confidence: 91%
See 1 more Smart Citation
“…In contrast, the S. hyicus recipients accepted the conjugative aadA-aphD-carrying resistance plasmids. Once again, this is in accordance with previous reports on resistance plasmids in S. hyicus and their structural similarities to resistance plasmids seen in other staphylococcal species from humans and animals [63,71,72,81]. Thus the spread of a certain plasmid or transposon may also be strongly influenced by factors in the host cells, such as restriction/modification systems or other plasmid exclusion systems which in the majority of cases remain to be identified in animal staphylococci.…”
Section: Horizontal Gene Transfersupporting
confidence: 91%
“…They identified an epidemic S. hyicus strain mediating resistance to penicillin, tetracycline, erythromycin, lincomycin, streptomycin, and chloramphenicol. Plasmids of this and other multiresistant S. hyicus strains were analysed in some detail in a number of different studies (see chapter 3) and it became obvious that the resistance plasmids identified in S. hyicus did not always correspond structurally to the respective plasmids known in human staphylococci [51,63,77,78,81,82]. In 1993, Wegener and Schwarz compared antibiotic resistances of S. hyicus isolates from diseased and healthy pigs [101].…”
Section: Staphylococcus Hyicusmentioning
confidence: 99%
“…Resistance to macrolide-lincosamide antibiotics was determined by the agar diffusion test [24] with disks (Becton-Dickinson, Heidelberg, Germany) containing erythromycin 15 pg, lincomycin 10 pg, or clindamycin 10 pg or tablets (Hiss Diagnostics, Freiburg, Germany) containing azithromycin 30 pg, spiramycin 200 pg or tylosin 150 pg. S. aureus RN4220 served as the recipient for plasmid pSES2 1 in protoplast transformation experiments [25]. During the further course of the study, the original S. hyicus strain, as well as S. aureus RN4220:pSES2 1 were grown on sheep blood agar (Oxoid) supplemented with erythromycin 30 mg/L.…”
Section: Bacterial Strains and Determination Of Macrolidelincosamide mentioning
confidence: 99%
“…The single plasmid found in the original S. hyicus isolate was transformed into S. aureus RN4220 by polyethylene glycol-mediated protoplast transformation [25,261; S. aureus RN4220:pSES21 transformants were subsequently selected on DM3 regeneration plates [26] supplemented with erythromycin 30 mg/L. The plasmid, designated pSES2 1, was isolated by affinity chromatography [27] (Qiagen Midi System, Hilden, Germany) and subjected to restriction endonuclease digests (Boehringer Mannheim, Germany).…”
Section: Plasmid Analysis and Southern Blot Hybridisationmentioning
confidence: 99%
“…A previously described modification of the alkaline lysis procedure [21] was used to prepare plasmid DNA from S. epidermidis 2 10. Restriction endonucleases (Boehringer) were used according to the manufacturer's recommendations.…”
Section: Plasmid Preparation and Southern Blot Hybridisationmentioning
confidence: 99%